Dynamic load balancing on non-homogeneous clusters - Naiouf, Ricardo Marcelo; De Giusti, Laura Cristina; Chichizola, Franco; De Giusti, Armando Eduardo (2006)
This paper discusses the dynamic static balancing of nonhomogenous cluster architectures, simultaneously analyzing the theoretical parallel speedup as well as the speedup experimentally obtained. A classical application (Parallel N-Queens) with a parallel solution algorithm, processing predominates upon communication, has been chosen so as to go deep in the load balancing aspects (dynamic static) without distortion of results caused by communication overhead. Four interconnected clusters have been used in which the machines within each cluster have homogeneous processors although different among clusters. Thus, the set can be seen as a N -processor heterogeneous cluster as a multicluster scheme with 4 subsets of homogeneous processors. At the same time, three forms of load distribution in the processors (Direct Static, Predictive Static Dynamic by Demand) have been studied, analyzing in each case parallel speedup load unbalancing regarding problem size the processors used.
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática-UNLP (Colección BIPA / Biblioteca.) -- Disponible también en línea (Cons. 02/06/2011)
Lecture Notes in Computer Science (Springer, 2006)
Keywords: PROCESAMIENTO PARALELO